influence of altitude and slope on the density of Asphodelus microcarpus Salzm & Viv. in the Mount of Tessala (Western Algeria) - El Bouhissi, Mayssara; Mehdadi, Zoheir; El Zerey, Wael (International Journal of Environment, 2016)
The change in the structure of species communities along environmental gradients is a privileged field of ecology as it allows exploring a continuous progression of situations often in a small area, in this context, we are interested in studying the impact of altitude and slope on the density and the recovery rate of Asphodelus microcarpus population in mountainous ecosystem. Asphodelus microcarpus is an ecological model, which allows us to have an idea about the degree of degradation in mountainous ecosystem, the density increases with advanced degradation stage. Analysis of variance revealed a highly significant difference (P = 0.001) between the 20 selected stations. The principal component analysis revealed that the density is important in low altitudes around 750 m where the slopes are average, this correlation is the result of human pressures that weaken the mountain of Tessala.International Journal of Environment Vol.5(3) 2016, pp.43-56